Pengaruh Variabel Keuangan dan Non Keuangan terhadap Underpricing pada Saham Perusahaan yang Melakukan Initial Public Offering di Bursa Efek Indonesia Periode 2024 (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the level of underpricing and the impact of financial variables (net profit margin and current ratio) and non-financial variables (auditor reputation and underwriter reputation) both partially and simultaneously on underpricing in the stocks of companies conducting initial public offerings (IPOs) on the Indonesia Stock Exchange. This research is quantitative with a descriptive statistical approach. Data were obtained from secondary company data, including financial statements and prospectuses of companies that IPOed in 2024, with a sample of 37 companies. The data analysis techniques include descriptive statistics, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination tests, using SPSS version 30. The results show that: (1) Net profit margin significantly affects underpricing, (2) Current ratio significantly affects underpricing, (3) Auditor reputation does not significantly affect underpricing, (4) Underwriter reputation does not significantly affect underpricing, (5) Simultaneously, net profit margin, current ratio, auditor reputation, and underwriter reputation significantly affect underpricing. The coefficient of determination (adjusted R²) of 0.273 indicates that 27.3% of the underpricing level can be explained by these four independent variables, while the remaining 72.7% is explained by other variables not tested in this study.